(3GdTaGAs - (3TQa Gdedc, CHh Ydj, GdQFjS GHf SjfG, GHf SjfG, GdMSjf Hf YHO Gddg Hf SjfG, J (B428(3g` (B1037(3es
(3ChdgG (B:s
(3ChdgG(B: (3Hjf GdfGaY hHjf GdNjQ eG gh hCf GdaQb Hjf GdVGO hHjf GdTQ eG gh hCf GdfGaY gh GdSHH GdehUd gOGjI Ydi GdNjQ hGdefaYIs
(3BNQgG (B:s
(3BNQgG(B: (3hjSf aj GdhdOGf jJhdGg cd hGMO ef GdhGdOjf HGdJQHjI, CeG GdhGdOI aHeG JMVfg, hCeG GdhGdO aHGdfabI hGdhdO CjVG jSf Ydjg NOeJgeG hWGYJgeG hEcHGQgeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 241s
(3cTa GdXfhf, L (B2: 1055s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs